(untitled) (Shahid Kirti Multidisciplinary Journal, 2026)
Nepal government increased the VAT rate from 10 percent to 13 percent in 2001/02 to finance the resource gap due to increased salary of its civil employees. The study has been undertaken to analyses the impact of this surge in the VAT rate. The study found that the rate could mobilize the revenue. It may be due to low rate of VAT in Nepal not only compared to the South Asian average but also global average. The performance of the VAT revenue administration improved slightly in terms of C efficiency ratio. The revenue collection jumped by nearly more than two times than the before rate change has been a plus point for the rate increment. The performance in other aspects like non-filers, excess credit and zero returns and VAT outstanding which affect the revenue mobilization has been deteriorated after the rate change. So, recommendations have been made to undertake a separate study in this field and in coming days the government should not revise the tax rate and government should stick on adopting present single rate instead of going to the multiple rate as demanded by the business community in Nepal.